Do Elections Accelerate the COVID-19 Pandemic? Evidence from a Natural Experiment - Ján Palguta; René Levínský; Samuel Škoda (Global Labor Organization (GLO), 2021)
Elections define representative democracies, but also produce spikes in physical mobility if voters need to travel to electoral rooms. In this paper, we examine whether large-scale, in-person elections propagate the spread of COVID-19. We exploit a natural experiment from the Czech Republic which biannually renews mandates in 1/3 of Senate constituencies rotating according to the 1995 election law. We show that in the second and third weeks after the 2020 elections (held on October 9-10), new COVID-19 infections grow significantly faster in voting compared to non-voting constituencies. A temporarily-related peak in hospital admissions and essentially no changes in test positivity rates suggest that the acceleration is not merely due to increased testing. The acceleration is absent in population above 65, consistently with strategic risk-avoidance by older voters. Our results have implications for postal voting reforms or postponing of large-scale, in-person (electoral) events during viral outbreaks.
Keywords: D70; D72; H0; H12; H75; I10; I18; 330; election; COVID-19; natural experiment; event study